THE ROLE OF TEACHER COMPETENCE TESTING TO INCREASE THE LEARNING QUALITY (PERAN UJI KOMPETENSI GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN) - Yuliany Yuliany (Fakultas Agama Islam Universitas Wiralodra, 2019)
This article aims to explore the effects on teacher competency testing to improve the learning quality. Deliberation efforts must be implemented to realize professional teachers: prosperous and competent. It is required absolutely to shape the system and quality eeucation practice. The law of Teachers and Lecturers as the policy to realize professional teachers. The law of teachers and lecturers decided the qualifications and certifications which will determine the quality and competence of teachers. Therefore, the implementation of certification will confront various obstacles. Besides the payment issue, various challenges and demands will emerge . How the government faces these challenges and demands will determine whether certification will succeed in improving the quality of teacher competencies. In other hand, teacher training and empowerment after certification will also determine whether certification activities will improve the quality of education or not. inappropriate coaching and empowerment do not close the possibility which occure certification activities as an activities to improve teacher welfare as an intermediate goal, while the ultimate goal of certification activities to improve the quality of education which is less attention from certification participants. Artikel ini bertujuan untuk menelusuri efek uji kompetensi guru dalam meningkatkan kualitas pembelajaran. Upaya yang sungguh-sungguh perlu dilaksanakan untuk mewujudkan guru yang profesional: sejahtera dan memiliki kompetensi. Hal ini merupakan syarat mutlak untuk menciptakan sistem dan praktik pendidikan yang bermutu. Undang-Undang Guru dan Dosen sebagai suatu kebijakan untuk mewujudkan guru profesional. UUGD yang menetapkan kualifikasi dan sertifikasi akan menentukan mutu dan kompetensi guru. Namun demikian, pelaksanaan sertifikasi akan menghadapi berbagai kendala. Di samping persoalan biaya, berbagai tantangan dan tuntutan juga akan muncul. Bagaimana cara pemerintah menghadapi tantangan dan tuntutan ini, akan menentukan apakah sertifikasi akan berhasil meningkatkan mutu kompetensi guru. Selain hal tersebut, pembinaan dan pemberdayaan guru pasca sertifikasi juga akan menentukan apakah kegiatan sertifikasi akan meningkatkan mutu pendidikan atau tidak. Pembinaan dan pemberdayaan yang kurang tepat tidak menutup kemungkinan akan menyebabkan kegiatan sertifikasi sekedar kegiatan untuk meningkatkan kesejahteraan guru sebagai tujuan antara, sementara tujuan akhir dari kegiatan sertifikasi untuk meningkatkan mutu pendidikan menjadi kurang mendapat perhatian dari peserta sertifikasi.